DEVELOPING THE TWO-TIER MULTIPLE CHOICE TESTS IN ENHANCING STUDENTS’ HIGHER-ORDER THINKING SKILLS ON HUMAN DIGESTIVE SYSTEM - Muhammad Jamhari (Universitas Bhinneka PGRI, 2021)
The aim of this study was to develop the two-tier multiple choice tests based on two indicators of higher-order thinking skills); level C4 and level C5. The subjects were: (1) an expert who validated the contents; (2) an expert who validated the constructs; (3) an expert who validated the items’ readability; and (4) eleventh graders. This was an RD study adopted from Borg Gall model. The results showed that: (1) validation of the contents indicated the mean score of 3.67 (very feasible category); (2) validation of the constructs indicated the mean score of 3.67 (very feasible category); (3) validation of the readability indicated the mean score of 3.50 (very feasible category); and (4) the students’ responses indicated that the tests were very good in small group tests of 93%. It was concluded that the two-tier multiple choice tests were very feasible in enhancing students’ higher-order thinking skills.